The Battle of Britain - Cawrhorne, Nigel (Arcturus, 2010)
The Battle of Britain presents in photographs the many aspects of the momentous campaign, from tactics, personalities, and aircraft to its effect on the lives of civilians. Lavishly illustrated, it is a tribute to a nation that pulled together in the face of overwhelming odds, and united, saved and guided the world.